The Effect of Rolling Temperature and Rolling Ratio on Hardness and TRS Boron Carbide 10% wt. B4C Reinforcement Copper Matrix Composite - ESKI, Özkan (Zain Publications, 2023)
In this study, the effect of adding boron carbide (B4C) 10% wt. and a grain size of 90 μm on the mechanical and physical properties, such as microstructure, hardness, and density, of cold pressed copper carbide (Cu-B4C) composites was investigated. To improve the mechanical properties of commercial copper powders with a particle size of 40 μm, B4C was added with a particle size of 90 μm, 10% wt. The (Cu-B4C) composites were sintered in argon gas at 850°C for 120 minutes. Some samples were hot-rolled at temperatures (600°C,700°C,800°C) and rolling pressures (10%,20%,30%,40%) and the values obtained before and after hot rolling were compared. Where a comparison was made between density, hardness, and bending resistance, the sintered products before and after hot rolling were studied by SEM-EDS analysis. In the obtained images, it was found that B4C was homogeneously dispersed in the (Cu) matrix. The hardness of the composites increased with the increase in B4C percentage, the decrease in density, and the increase in porosity of the original samples. The hardness values of the rolled samples increased with increasing rolling temperatures (600°C,700°C,800°C) and rolling pressure ratios (10%,20%,30%,40%) and bending strength decreased with increasing rolling temperatures and pressure ratios for all samples that have been subjected to these changes.